2010
DOI: 10.1134/s1070428010060011
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1-hetarylethylphosphonates

Abstract: Synthesis of 1-Hetarylethylphosphonates -[via Pd-catalyzed reduction of corresponding ,-unsaturated precursors using ammonium formate]. -(GULYUKINA*, N. S.; BELETSKAYA, I. P.; Russ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The traditional Pd catalysts continue to have widespread application, and thus it is interesting to note that hydrogenation of 2-methylquinoline in the presence of Pd/C in trifluoroacetic acid afforded 2-methyl-5,6,7,8-tetrahydroquinoline in almost quantitative yield . Similarly, quinoline derivatives bearing a phosphonate moiety were also hydrogenated effectively in the presence of Pd/C and excess of ammonium formate to afford the corresponding 1,2,3,4-tetrahydroquinolines . In a recent article, it was reported that the hydrogenation of polysubstituted quinoline derivatives in the presence of Pd/C or Pd(OH) 2 afforded the corresponding 1,2,3,4-tetrahydroquinolines…”
Section: Synthesis Of 1234-tetrahydroquinolines Involving the Partial...mentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional Pd catalysts continue to have widespread application, and thus it is interesting to note that hydrogenation of 2-methylquinoline in the presence of Pd/C in trifluoroacetic acid afforded 2-methyl-5,6,7,8-tetrahydroquinoline in almost quantitative yield . Similarly, quinoline derivatives bearing a phosphonate moiety were also hydrogenated effectively in the presence of Pd/C and excess of ammonium formate to afford the corresponding 1,2,3,4-tetrahydroquinolines . In a recent article, it was reported that the hydrogenation of polysubstituted quinoline derivatives in the presence of Pd/C or Pd(OH) 2 afforded the corresponding 1,2,3,4-tetrahydroquinolines…”
Section: Synthesis Of 1234-tetrahydroquinolines Involving the Partial...mentioning
confidence: 99%
“…517 Similarly, quinoline derivatives bearing a phosphonate moiety were also hydrogenated effectively in the presence of Pd/C and excess of ammonium formate to afford the corresponding 1,2,3,4-tetrahydroquinolines. 518 In a recent article, it was reported that the hydrogenation of polysubstituted quinoline derivatives in the presence of Pd/C or Pd(OH) 2 afforded the corresponding 1,2,3,4-tetrahydroquinolines. 519 Kobayashi and co-workers also developed a polymer incarcerated platinum (PI Pt) catalyst similar to the Pd-containing one previously discussed.…”
Section: Partial Hydrogenation Of Quinolines To Racemic 1234-tetrahyd...mentioning
confidence: 99%
“…Impressive achievements have been reached in this area by applying catalysts based on noble metal NPs (e.g., Pd, Pt, Rh, , Ru, , Ir, ,, and Au , ). However, the high and volatile price associated with the low availability of precious metals has boosted the interest to exploit cheap and earth-abundant metals for the development of novel catalysts in recent times, although, to date, to a limited extent for the hydrogenation of quinolines.…”
Section: Introductionmentioning
confidence: 99%